Perancangan Interior Kontainer Sebagai Sarana Edukasi Di Rusun Sombo Surabaya (Mini Library â Refunction Container) - Prajogo, Maria Valenciana Utari (Intra, 2015)
Surabaya is the second biggest city in Indonesia. With itâs majority society on productive age, Surabaya has been declared as the City of Literacy since June 2014 by the city government. The realization of this City of Literacy has become a commitment part of Tri Risma Harini as the Major of Surabaya, not only to focus on infrastructure development, but also to focus on the human development index. The raising of this Literacy cityâs program has been marked by the establishment of 400 Taman Baca Masyarakat (TBM) in each sub-district with 15 minutes daily reading which has become a routines, so that the children must be facilitated with kind of interesting reading space,with the purpose is to make reading no longer a boring.. The designer chooses container which is no longer functional in the harbor, to be conversed from a goods diversion into an educational facility for an early childhood. Based on the flexibility of dimension, design and mobility, this container library will be interesting and advantageous in Sombo Flats, especially for early childhood kids in Surabaya City.